Analisis Daya Saing Komparatif dan Kompetitif Ekspor Komoditas Batu Bara Tiga Negara Berkembang (Indonesia, Afrika Selatan dan Kolombia) - Sifa Yulia; Ika Chandriyanti (Ecoplan, 2021)
Coal is a fuel made from fossils, which hold an essential part of the energy for power plants and serves as a staple fuel for steel and cement production. Indonesia, South Africa, and Colombia are developing countries that took part in the largest coal exporters in the world. The purpose of this study is to analyze the three developing countries in coal exporting competitiveness, Indonesia, South Africa, and Colombia, in terms of comparative advantage or competitive advantage and times of the trade specialization index, as well as compare the exports and imports of coal from the three countries and export developments. This study will be using secondary data within a period of fifteen years (2004 – 2018). The data analysis methods used in this study are based on the Balassa Index of Revealed Comparative Advantage (RCA) and the Trade Specialization Index (TSI). The research from RCA showed that Indonesia doesn’t have a comparative advantage in contrast to South Africa, but Indonesia has a comparative advantage collated with Colombia. Based on the study held by TSI, the three developing countries are presumed to have strong competitiveness and tend to succeed in becoming coal exporting countries.